Pengaruh Kecerdasan Emosional dan Motivasi Belajar terhadap Adaptabilitas Karir Mahasiswa - Budiarti, Sangdwika; Wahyu Wirawan , Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Career adaptability represents a critical competency for university students navigating labor market challenges and dynamicsIntrinsic elements like emotional intelligence and motivation for learning influence this competency. This research examined the impact of emotional intelligence and learning motivation on career adaptability in students enrolled in the Office Administration Education Program at Universitas Negeri Semarang. A quantitative explanatory design was adopted. The population comprised 121 students, all serving as respondents. The data gathering employed a survey, and the examination was performed by multiple linear regression. Emotional intelligence had a substantial and beneficial impact on job adaptability (regression coefficient = 0.366; p < 0.001). Motivation to learn also showed a strong positive effect (β = 0.449, p < 0.001). Together with emotional intelligence, these two variables significantly predicted career adaptability, explaining 90.8% of the variance (F = 580.860, R^2 = 0.908). This emphasizes the essential role both elements play in enhancing student career preparedness.